The effects of reward on children's Stroop performance: Interactions with temperament. Issue 1 (13th September 2021) - Bryant, Lauren J.; Cuevas, Kimberly
Abstract: The effects of rewards on executive function (EF) reflect bidirectional interactions among motivational and executive systems that vary with age and temperament. However, methodological limitations hinder understanding of the precise influences of incentives on early EF, including the role of reward sensitivity. In this within‐subjects study, ninety‐three 3.5‐ to 5‐year‐olds (42 girls; 22% Hispanic; 78% White) residing in the United States completed equivalent EF measures (Stroop and non‐Stroop phases) in both rewarded and non‐rewarded conditions. Rewards enhanced Stroop accuracy and slowed overall response times ( d s = 0.29–0.40). Critically, children with low parent‐reported reward sensitivity exhibited greater reward‐based increases in Stroop accuracy ( r  = −.30). These findings provide valuable insights on early motivation–cognition integration, highlighting temperament as a mechanism underlying these interactions.